A Robust, GFP-Orthogonal Photoswitchable Inhibitor Scaffold Extends Optical Control over the Microtubule Cytoskeleton. Issue 2 (18th February 2021) - Gao, Li; Meiring, Joyce C.M.; Kraus, Yvonne; Wranik, Maximilian; Weinert, Tobias; Pritzl, Stefanie D.; Bingham, Rebekkah; Ntouliou, Evangelia; Jansen, Klara I.; Olieric, Natacha; Standfuss, Jörg; Kapitein, Lukas C.; et al.
Summary: Optically controlled chemical reagents, termed "photopharmaceuticals, " are powerful tools for precise spatiotemporal control of proteins particularly when genetic methods, such as knockouts or optogenetics are not viable options. However, current photopharmaceutical scaffolds, such as azobenzenes are intolerant of GFP/YFP imaging and are metabolically labile, posing severe limitations for biological use. We rationally designed a photoswitchable "SBT" scaffold to overcome these problems, then derivatized it to create exceptionally metabolically robust and fully GFP/YFP-orthogonal "SBTub" photopharmaceutical tubulin inhibitors. Lead compound SBTub3 allows temporally reversible, cell-precise, and even subcellularly precise photomodulation of microtubule dynamics, organization, and microtubule-dependent processes. By overcoming the previous limitations of microtubule photopharmaceuticals, SBTubs offer powerful applications in cell biology, and their robustness and druglikeness are favorable for intracellular biological control in in vivo applications. We furthermore expect that the robustness and imaging orthogonality of the SBT scaffold will inspire other derivatizations directed at extending the photocontrol of a range of other biological targets. Graphical Abstract: Highlights: SBTub3 photocontrols microtubule dynamics, organization, and dependent processes Microtubule photocontrol is cell and sub-cellularly precise and temporally reversible SBT photocontrol is orthogonal to GFP/YFP imaging and SBTs are metabolically stable The SBT scaffold is promising for photopharmaceuticals for other protein targets Abstract : Photocontrollable reagents have unique potential as high spatiotemporal precision modulators of biological systems. Here, Gao et al. demonstrate a GFP-orthogonal and metabolically stable photoswitch that allows optical control over microtubule dynamics and architecture with subcellular resolution. The photoswitch scaffold also offers new possibilities for photopharmaceutical design against other targets.